Low Carbon Energy Supply Trends, Technology, Management (Green Energy and Technology,, 2018)
This book focuses on recent trends in the areas of green and renewable energy, especially as applied to the carbon footprint of energy production, transmission, and use. Discussing the latest developments and advances in the materials and processes involved in energy generation, transmission, distribution and storage, with a particular focus on the management and policies related to these systems, it is a valuable resource for researchers, practitioners, and policy makers working in these areas.